Optimalisasi Penggunaan Web Desaku Melalui Transformasi Digital - Wirman, Aditya; Yunita, Alpia Salwa; Herald, Wahyudhi; Saputro, Wahyu Catur; Maryesti Anita Agustina Bonisau, Maryesti Anita Agustina; Pasaribu, Kiki Adelia; Fadilah, Riyan; Surya, M. Bima Annasta; Pahlawan, Gusti Rama; Ginting, Arwanto Harimas (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
This article discusses efforts to optimize the web desaku platform through digitaltransformation in village government.The web desaku platform village Cikumpay consistsof village profiles, e-commerce and daily village news which need to be optimized so thatits application is useful for village government as a tool to improve the quality ofCikumpay village government services, as well as for the village community who find itseasy to get information about villagesResults research conducted by the author showsthat the existence of the web desaku is known. But its use has not been maximized byvillage officials due to a lack of understanding of how to fill out the plaform on it andalso incomplete data. The low quality of village officials human resources is the mainchallenge that the author mush face in optimizing the use of the web desaku website.Thus,this article attempts to break down the problems faced by village officials throughactivities carried out by the author starting from mapping the understanding of villageofficials,interview and brainstorming activities as well as guidance activities on fillingout the web desaku platform. The implications of research can be used as a guide forfurther development in intergration digitalization in village government managemen.